Lossless Compression Performance of a Simple Counter-Based Entropy Coder - Armein Z.R. Langi (LPPM ITB, 2011)
This paper describes the performance of a simple counter based entropy coder, as compared to other entropy coders, especially Huffman coder. Lossless data compression, such as Huffman coder and arithmetic coder, are designed to perform well over a wide range of data entropy. As a result, the coders require significant computational resources that could be the bottleneck of a compression implementation performance. In contrast, counter-based coders are designed to be optimal on a limited entropy range only. This paper shows the encoding and decoding process of counter-based coder can be simple and fast, very suitable for hardware and software implementations. It also reports that the performance of the designed coder is comparable to that of a much more complex Huffman coder.